Readiness to Change Over Time: Change Commitment and Change Efficacy in a Workplace Health-Promotion Trial - Helfrich, Christian D.; Kohn, Marlana J.; Stapleton, Austin; Allen, Claire L.; Hammerback, Kristen Elizabeth; Chan, K. C. Gary; Parrish, Amanda T.; Ryan, Daron E.; Weiner, Bryan J.; Harris, Jeffrey R.; Hannon, Peggy A. (Frontiers in Public Health, 2018)
Introduction Organizational readiness to change may be a key determinant of implementation success and a mediator of the effectiveness of implementation interventions. If organizational readiness can be reliably and validly assessed at the outset of a change initiative, it could be used to assess the effectiveness of implementation-support activities by measuring changes in readiness factors over time. Methods We analyzed two waves of readiness-to-change survey data collected as part of a three-arm, randomized controlled trial to implement evidence-based health promotion practices in small worksites in low-wage industries. We measured five readiness factors: context (favorable broader conditions); change valence (valuing health promotion); information assessment (demands and resources to implement health promotion); change commitment (an intention to implement health promotion); and change efficacy (a belief in shared ability to implement health promotion). We expected commitment and efficacy to increase at intervention sites along with their self-reported effort to implement health promotion practices, termed wellness-program effort. We compared means between baseline and 15 months, and between intervention and control sites. We used linear regression to test whether intervention and control sites differed in their change-readiness scores over time. Results Only context and change commitment met reliability thresholds. Change commitment declined significantly for both control (-0.39) and interventions sites (-0.29) from baseline to 15 months, while context did not change for either. Only wellness program effort at 15 months, but not at baseline, differed significantly between control and intervention sites (1.20 controls, 2.02 intervention). Regression analyses resulted in two significant differences between intervention and control sites in changes from baseline to 15 months: (1) intervention sites exhibited significantly smaller change in context scores relative to control sites over time, and (2) intervention sites exhibited significantly higher changes in wellness program effort relative to control sites. Discussion Contrary to our hypothesis, change commitment declined significantly at both Healthlinks and control sites, even as wellness-program effort increased significantly at HealthLinks sites. Regression to the mean may explain the decline in change commitment. Future research needs to assess whether baseline commitment is an independent predictor of wellness-program effort or an effect modifier of the HealthLinks intervention.